1977
DOI: 10.1113/jphysiol.1977.sp012062
|View full text |Cite
|
Sign up to set email alerts
|

The relation between tidal volume and inspiratory and expiratory times during steady‐state carbon dioxide inhalation in man

Abstract: TI, and (c)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 30 publications
(74 reference statements)
8
63
0
Order By: Relevance
“…Some controversy regarding the latter finding persists (Jennett, Russell & Warnock, 1974), as does controversy regarding the decrease in expiratory duration at low tidal volumes (Clark & Euler, 1972). However, Gardner's (1977) recent study appears to have confirmed the pattern of breathing described above for steady-state CO2 inhalation. On the other hand in his studies on awake cats, Gautier (1975) showed that steady-state hypoxia shortened inspiratory time, a finding that contrasted with his earlier studies of hypercapnia.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Some controversy regarding the latter finding persists (Jennett, Russell & Warnock, 1974), as does controversy regarding the decrease in expiratory duration at low tidal volumes (Clark & Euler, 1972). However, Gardner's (1977) recent study appears to have confirmed the pattern of breathing described above for steady-state CO2 inhalation. On the other hand in his studies on awake cats, Gautier (1975) showed that steady-state hypoxia shortened inspiratory time, a finding that contrasted with his earlier studies of hypercapnia.…”
Section: Introductionmentioning
confidence: 76%
“…Remmers (1976) has interpreted this hypercapnic effect as an augmentation of inspiratory drive and suppression of expiratory braking without alteration of the timing of the inspiratory 'off-switch'. At higher tidal volumes, hypercapnia appears also to shorten inspiratory time (Clark & Euler, 1972;Gardner, 1977). Some controversy regarding the latter finding persists (Jennett, Russell & Warnock, 1974), as does controversy regarding the decrease in expiratory duration at low tidal volumes (Clark & Euler, 1972).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Subdivisions of ventilation Minute volume is the product of tidal volume and frequency (VE = VT xf) and separate measurement of these components is important in the analysis of control of breathing (Hey, Lloyd, Cunningham, Jukes & Bolton, 1966;Clark & von Euler, 1972;Newsom-Davies & Stagg, 1975). Ventilatory responses to exercise and carbon dioxide have been investigated in this way (Cunningham & Gardner, 1972;Cunningham, Drysdale & Gardner, 1977;Gardner, 1977) as have those to vagus nerve blockade (Guz, Noble, Widdicombe, Trenchard, Mushin & Makey, 1966; and certain drugs (Gautier & Gaudy, 1978).…”
Section: Theoretical Problemsmentioning
confidence: 99%
“…However, other authors have shown in animals that, whereas a major component of the ventilatory response is mediated via the arterial chemoreceptors, a significant component is the result of direct effects on the central nervous system (Eldridge & Gill-Kumar, 1980;Winn et al, 1979). Folgering (1980) (Hey et al, 1966;Cunningham & Gardner, 1977;Gardner, 1977 (Bailey, 1959).…”
Section: Introductionmentioning
confidence: 99%